2020
DOI: 10.3389/fendo.2020.578194
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Lipid Metabolism on Osteoblast Function

Abstract: The skeleton is a dynamic and metabolically active organ with the capacity to influence whole body metabolism. This newly recognized function has propagated interest in the connection between bone health and metabolic dysfunction. Osteoblasts, the specialized mesenchymal cells responsible for the production of bone matrix and mineralization, rely on multiple fuel sources. The utilization of glucose by osteoblasts has long been a focus of research, however, lipids and their derivatives, are increasingly recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 186 publications
(244 reference statements)
0
50
1
Order By: Relevance
“…In addition, lipids and their derivatives can activated osteoblasts via selective lipid receptors and catabolic enzymes for the internalization and utilization of circulating lipids. Dyslipidaemia and lipid homeostasis disruption can impair osteoblast function and accelerate osteoclast activity 5,6 . Targeting lipid metabolism with a statin has been shown to improve bone density and quality in metabolic bone diseases 7 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, lipids and their derivatives can activated osteoblasts via selective lipid receptors and catabolic enzymes for the internalization and utilization of circulating lipids. Dyslipidaemia and lipid homeostasis disruption can impair osteoblast function and accelerate osteoclast activity 5,6 . Targeting lipid metabolism with a statin has been shown to improve bone density and quality in metabolic bone diseases 7 …”
Section: Introductionmentioning
confidence: 99%
“…Histological studies indicated that both mature osteoblasts and differentiating osteoblast progenitors contain stored lipids. Moreover, in vivo and in vitro studies showed that osteoblasts uptake circulating lipoproteins and free fatty acids [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, proteins participating in energy production, ACSL3 and ACLS4 (2.17, 2.03-fold increase, respectively) as members of β-oxidation, ATP5MG (2.11-fold increase) responsible for ATP synthesis in mitochondria, NDUFS1, NDUFS3, NDUFV2, and NDUFAF2 (1.02, 1.01, 1.1, 2.97-fold increase, respectively) involved in electron transport chain in mitochondria, SDHA and SDHB (1.13, 1.47-fold increase, respectively) enzymes of TCA cycle. Bone remodeling is an energy-consuming process due to the synthesis of extracellular matrix proteins and the accumulation of mineral ions for hydroxyapatite crystal formation [ 95 ]. Interestingly, the authors reported that insulin signaling affected both bone metabolism and energy production [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bone is a dynamic endocrine organ that regulates its own and even the whole body’s steady-state balance ( Alekos et al, 2020 ). Bone modeling and remodeling are strictly controlled by many factors, including lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Among the bone components, chicken cortical bone contains a higher fatty acid content than cancellous bone, which allows the intensity of metabolic activity to be maintained ( Dolegowska et al, 2006 ; Liu et al, 2021 ). In addition, the utilization of fatty acids in bone is comparable to that in tissues with more a classic fatty acid metabolism ( Alekos et al, 2020 ). Increasing evidence shows that there is a close correlation between bone fat and many bone diseases ( Bermeo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%